High yielding efficient cultivation techniques for rubber plantations on a large sclae in Xishuangbanna state farms - Tianxi He; 6aDongfeng Gao; Yiming Qu (Proceedings of IRRDB Conference: NR Industry: Responding to Globalization, 7-8 September 2004, Kunming International Convention & Exhibition Center, China. pp.119-127.)
In Xishuangbanna state farms, rubber trees are planted in hilly areas located at the northern edge of tropics, where the natural conditions for rubber growing are much worse than those in any other traditional rubber planting areas in the world. However, based on the characteristics of the local natural conditions, a full set of rubber growing techniques for high-yield and high-efficiency, suitable for the climatic characteristics in Xishuangbanna, has been established and extended. Dried rubber yield per unite exceeded 1800kg/ha, continuously for nine years from 1995 to 2003, especially in 2002 and 2003, created seperately the new records of 2048kg/ha and 2072kg/ha at the tapped area of 50,700 ha and 52,000ha. And the annual dried rubber production per tapper separately averaged 5.46 tons and 5.63 t. Rubber plantations in Xishuangbanna state farms have become the top-ranking ones with high-efficiency in the world.
Keywords: Rubber planting; Yield